Paleosuperfícies e perfis bauxíticos no Planalto de Poços de Caldas, São Paulo/Minas Gerais, Brasil - Leonardi, Fernanda Aparecida; Ladeira, Francisco Sérgio Bernarde; dos Santos, Marcilene [UNESP] (My University, 2011)
This work has the objective of correlating altitude with the bauxite profiles in the Poços de Caldas Plateau in order to identify paleosurfaces. Then, bauxite profiles found in the Plateau have been classified and mapped through DEM. Three different types of bauxite profiles are highlighted in the area: (1) Rim Profiles which are well-developed and thick and are located in the areas of highest altitude in the Plateau; (2) Plateau Profiles which are not very thick and very clayey, normally appear in the lower portion of the landscape; (3) Reworked Profiles, characterized by bauxite reworked fragments composed by similar materials found in the tops of Rim and Plateau Profiles. After relating altitude to the constituting materials of the bauxite profiles, it is noticed that there are occurrences of Rim Bauxite Profiles located in altitudes of Plateau Profiles and Reworked Profiles located over Rim Profiles, above 1,400 meters of altitude. In the opposite direction, tops of the same elevation are found, where there should be Rim Profiles, there are rocky outcrops observed in field, without any evidence of laterite profiles. It is concluded, therefore, that the elevation rates by themselves, at least in this area, are not good enough references to determine the existence and distribution of paleosurfaces.
Paleosurfaces and bauxite profiles in the Poços de Caldas Plateau, São Paulo/Minas Gerais, Brazil
Keywords: Bauxite profiles; Brazil; Minas Gerais; Paleosurface; Poços de Caldas; São Paulo; altitude; bauxite; digital elevation model; landscape; laterite; Pocos de Caldas; Sao Paulo [Brazil]